HUBUNGAN ANTARA GANGGUAN KECEMASAN DAN DISFUNGSI GASTROINTESTINAL PADA KALANGAN REMAJA - Aliyya Amanda Salsabila; Azil Valino Sabri Mulia; Bunga Rahmi; Mutiara Anissa; Dessy Abdullah (Nusantara Hasana Journal, 2025)
Anxiety disorders are a common mental health problem that affects many adolescents and young adults and can negatively impact both short-term and long-term health. Functional gastrointestinal disorder (FGID) occurs in Indonesian adolescents with a prevalence of 40.85% (Ministry of Health, 2020) and is often affected by anxiety through the communication pathways between the brain and intestines. This interaction means that anxiety worsens digestion and digestive problems increase anxiety. It reflects the complex interplay between psychological, biological, and social factors. The purpose of this systematic review was to review the current literature on the relationship between anxiety disorders and gastrointestinal dysfunction in adolescents, including mechanisms, risk factors, and diagnostic and treatment approaches. This systematic review used the PRISMA-P 2020 (Preferred Reporting Items for Systemic Review and Meta-Analysis Protocols) protocols. The study was collected through a search of Pubmed, EBSCO, Zendy, and Proquest source data from 2014 to 2020. Keyword search uses the PICO-S (Population Intervention Compare Outcome-Study design) technique. It found 225 studies and 18 studies were included in this study. Gastrointestinal (GI) disorders are often closely related to anxiety through the brain-intestinal axis, where anxiety can affect GI functions such as intestinal motility, visceral sensitivity, and microbiota composition. This can lead to conditions such as irritable bowel syndrome (IBS), acid reflux, and other indigestion. In contrast, GI disorders can also frustrate anxiety, creating mutually reinforcing cycles. The treatment of gastrointestinal disorders and anxiety from the results of our research is psychological therapy, medical treatment and pharmacological treatment such as corticosteroids and aminosalylates. Anxiety is a serious mental illness that often manifests as physical symptoms, such as heart palpitations and indigestion. It is related to the brain axis, where chronic and anxiety can affect gut motility, visceral sensitivity, and the gut microbiome. According to research, the gut microbiota plays an important role in depression and anxiety, making it a potential target for treatment and recovery. Web-based therapies, such as cognitive behavioral therapy, are effective in treating gastrointestinal disorders and anxiety and also some medications such as corticosteroids.